2022
DOI: 10.3389/fped.2022.965739
|View full text |Cite
|
Sign up to set email alerts
|

Is the six-minute walk test still reliable compared to cardiopulmonary exercise test for exercise capacity in children with congenital heart disease?

Abstract: ObjectivesWe aimed to assess the validity of the six-minute walk test (6MWT) to reflect the functional capacity of children with congenital heart disease (CHD), evaluate a possible correlation between the 6MWT distance with cardiopulmonary exercise test (CPET) variables, as well as to find a cutoff value to stratification the physical fitness in this population.MethodsWe enrolled 459 children with CHD, 6–18 years old, who performed a complete CPET and 6MWT on the same day in a cross-sectional observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…These findings may be due to particular group or due to more stress associated with ergospirometric testing like treadmill [40]. In addition, another study conducted to evaluate the accuracy of the six-minute walk test in children with congenital heart disease determined specific values that can be used to categorize physical fitness and found connections with variables from the cardiopulmonary exercise test stressing on the use of the traditional testing like 6-minute walk testing as compared to treadmill Ergospirometric testing [41]. In addition, a cross-sectional study was conducted to compare the performance of obese/overweight children and normal-weight children in the 6-minute walk test and their hemodynamic parameters and found that OW&OB children had lower performance and experienced higher hemodynamic stress and, in this way, highlighting the significance of early intervention in order to reduce future health risks using more latest Ergospirometric testing [42].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be due to particular group or due to more stress associated with ergospirometric testing like treadmill [40]. In addition, another study conducted to evaluate the accuracy of the six-minute walk test in children with congenital heart disease determined specific values that can be used to categorize physical fitness and found connections with variables from the cardiopulmonary exercise test stressing on the use of the traditional testing like 6-minute walk testing as compared to treadmill Ergospirometric testing [41]. In addition, a cross-sectional study was conducted to compare the performance of obese/overweight children and normal-weight children in the 6-minute walk test and their hemodynamic parameters and found that OW&OB children had lower performance and experienced higher hemodynamic stress and, in this way, highlighting the significance of early intervention in order to reduce future health risks using more latest Ergospirometric testing [42].…”
Section: Discussionmentioning
confidence: 99%